Observation and Discussion on the History of Maritime Archipelago - Ali, Ismail (TAWARIKH, 2010)
ABSTRACT: Traditionally, ocean is seen as the source of inspiration in the quest for truth that denies the theory of worldview which is always related to myths and superstitions. Ocean has its advantage to tie relationship between nations, to form the will of togetherness, to understand each other as well as to generate wealth. It is priceless treasure which cannot be traded and changed. On the contrary, ocean can also be regarded as a conflict zone that has brought the fall of many ancient traditional civilizations and caused the distant relationship between nations. In relation to this, this article will review the importance of observation relating to maritime aspects of this region and the ability of maritime in re-uniting modern countries of South East Asia that have destroyed due to past colonization. To realize the mission and vision of uniting the nations of this region, a paradigm shift in the government policy as well as in the mind of the people should first be done, i.e. to see oceans as an uniting factor not as separator. In a bigger framework, all nations of this region should instil the determination and awareness that the historical and cultural maritime of Southeast Asia belongs to everybody and it is the joint heritage of every states and nations in this region. Â Â Â Â Â Â KEY WORDS: Ocean, united nation, islands of South East Asia, archipelago, and the history of maritime.About the Author: Assoc. Prof. Dr. Ismail Ali is a Lecturer at the Programme of History, School of Social Sciences UMS (Malaysia University of Sabah), Jalan Beg Berkunci 273, 88999 Kota Kinabalu, Sabah, Malaysia. He can be reached at: ismailrc@ums.edu.myHow to cite this article? Ali, Ismail. (2010). âObservation and Discussion on the History of Maritime Archipelagoâ in TAWARIKH: International Journal for Historical Studies, Vol.1(2) April, pp.139-158. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 14, 2010); Revised (March 19, 2010); and Published (April 28, 2010).